Apoptosis Effect of Ethanol Extract Soursop Leaves On WiDr Cancer Cell Line - Yoni Astuti; Wahyu Joko Priambodo; Sabtanti Harimukti; Agus Suharto (Universitas Muhammadiyah Yogyakarta, 2021)
Apoptosis is a critical physiological process responsible for the homeostatic mechanism and maintenance of cell populations in tissues. Due to the close correlation between the mechanism of apoptosis and the effect of anticancer agents, extensive research has been done on this mode of cell death. Annona muricata has a significant antiproliferative effect on some cancer cells. This research carried out to explore the apoptosis effect of ethanol extract soursop leaves from Tawangmangu on WiDr cancer cell line. Methods To gain the ethanol extract of soursop leaves use maserasi method. To calculate the death cell used colouring Tryphan blue. The result showed that the average of death cell at dose IC 50 in 24 hrs was (6.35±2.05) 104 in 48 hours were (11.1±1.27) 104. meanwhile that the average of death cell at dose ½ IC in 24 hours were (6.15±0.64)104 and (10.25±1.59) 104. The Increasing of death cell at dose IC 50 during 24 hours were 1,71 times and at dose ½ IC 50 were 1,67 times. Conclusion: Ethanol extract Annona muricata from Tawangmangu able to increase death cell around 1,71 times per hours in IC50 and 1,67 in 1/2IC50 on WiDr cell line.